A structural computing model for dynamic service-based systems - King, Peter (2004)
Traditional techniques for Programming in the Large, especially Object- Oriented approaches, have been used for a considerable time and with great success in the implementation of service-based information systems. However, the systems for which these techniques have been used are static, in that the services and the data available to users are fixed by the system, with a strict separation between system and user. Our interest lies in currently emerging dynamic systems, where both the data and the services available to users are freely extensible by the users and the strict distinction between system and user no longer exists. We describe why traditional object-oriented approaches are not suitable for modelling such dynamic systems. We discuss a new architectural model, the Information Unit Hypermedia Model, IUHM, which we have designed for modelling and implementing such dynamic systems. IUHM is based upon the application of structural computing to a hypermedia-like structure, which thereby operates as a service-based architecture. We discuss the details of this model, and illustrate its features by describing some aspects of a large-scale system, built using this architecture.